2021
DOI: 10.31729/jnma.6013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malnutrition among Elderly People Living in a Rural Area of Nepal

Abstract: Introduction: Elderly population is more likely to suffer from malnutrition due to aging-associated factors that influence nutritional status like loss of appetite, swallowing difficulties, digestive problems, and chronic illness. There is insufficient information related to the nutritional status of the elderly in Nepal. Hence, this study aims to determine the prevalence of malnutrition among elderly people living in the rural area of the Kavrepalanchok district. Methods: A descriptive cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Similar findings were found in studies. 8 , 15 , 16 Another study conducted in India too shows high prevalence of at risk of malnourished. 17 However slight differences was observed in a study conducted in another hospital in Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were found in studies. 8 , 15 , 16 Another study conducted in India too shows high prevalence of at risk of malnourished. 17 However slight differences was observed in a study conducted in another hospital in Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…For example, among older individuals in Nepal, the prevalence of malnutrition and those at risk of malnutrition were determined to be 11.6% and 49.7%, respectively. 34 Additionally, a reported prevalence of malnutrition or being at risk for malnutrition was 71.6% among older Vietnamese patients with dysphagia. 35 The disparity in nutritional status across countries may be influenced by factors such as eating problems, health conditions, poor socioeconomic status, and living and marital status, including living alone or being unmarried, widowed, or divorced.…”
Section: Discussionmentioning
confidence: 99%
“… 20 - 23 For example, a study in Nepal in 2021 reported 11.6% with undernutrition and 49.7% at risk of undernutrition. 21 However, the prevalence of undernutrition among hospitalized elderly patients in Egypt in 2013 was 18%, 22 and in Lebanon in 2014, it was 6.1%. 23 These discrepancies are likely linked to variations in the types of diseases and hospitalization conditions.…”
Section: Discussionmentioning
confidence: 99%